THE NEW PSEUDO-SUFI ORDER OF THE MAJELIS SHALAWAT AMONG URBAN MUSLIMS IN EAST JAVA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
This article analyzes a new variant of urban Sufism with specific reference to majelis shalawat (shalawat group) as the new-pseudo Sufi order in Indonesia. It focuses on three majelis shalawat: Majelis Shalawat Kubro, Majelis Shalawat Muhammad, and Majelis Shalawat Adlimiyah. Employing field research, this article argues that the three shalawat groups that flourish in East Java have specific characters unique to the groups. They locate the silsilah (chain of lineage) as an important part in establishing the institution, doctrines, and Sufism practices among their adherents. The aspect of Sufism transmission is articulated as experiencing Sufism through living as inspired by Abu al-Qasim al-Junayd, not as told to them by ‘ulama who theorize Sufism. Furthermore, doing Sufism means a process of experiencing supported by two Sufism traditions at once; they are vivid interconnection (rabitat bi al-suhbah) and virtual interconnection (rabitah bi al-ghayb). The application of the two rabitahs locates a Sufi travellers in a full consciousness (yaqzah) far from self-disappearance (al-fana’ fi al-shaykh). With all of its characteristics, the three shalawat groups generate new variants of Sufi practice that can be considered as new Sufi order.